Influence of surface modification with D205 dye on charge dynamics of hybrid ZnO nanorods/polymer solar cells - Pipat Ruankham (2018)
© 2016 Taylor & Francis Group, LLC. Influence of surface modification with D205 dye on charge dynamics of hybrid solar cells based on ZnO nanorods and poly(3-hexylthiophene) or P3HT was investigated. Electrochemical impedance spectroscopy analysis reveals that ZnO nanorods/D205/P3HT device shows longer effective lifetime (less charge recombination) in comparison with ZnO nanorods/P3HT one. Moreover, transit time of electrons travelling to the electrode for the D205-modified device is shorter than that of the unmodified one. These results indicate that the adsorption of D205 dye promotes efficient charge collection, leading to the improvement in fill factor. The surface modification efficiently enhances charge dynamics of hybrid ZnO/P3HT devices.